The impatient woman's guide to getting pregnant - Twenge, Jean M., 1971- (Free Press, 2012)
"The Impatient Woman's Guide to Getting Pregnant is a complete guide to getting pregnant--the medical, psychological, social, and sexual aspects, told in a straight-forward, funny, and compassionate manner, like talking to a good friend who's been through it all."--